Bilateral histone deacetylase 1 and 2 activity and enrichment at unique genes following induction of long‐term potentiation in vivo. Issue 4 (30th December 2020) - Kyrke‐Smith, Madeleine; Logan, Barbara; Abraham, Wickliffe C.; Williams, Joanna M.
Abstract: Long‐term potentiation (LTP) is a synaptic plasticity mechanism critical to long‐term memory. LTP induced in vivo is characterized by altered transcriptional activity, including a period of upregulation of gene expression which is followed by a later dominant downregulation. This temporal shift to downregulated gene expression is predicted to be partly mediated by epigenetic inhibitors of gene expression, such as histone deacetylases (HDACs). Further, pharmacological inhibitors of HDAC activity have previously been shown to enhance LTP persistence in vitro. To explore the contribution of HDACs to the persistence of LTP in vivo, we examined HDAC1 and HDAC2 activity over a 24 hr period following unilateral LTP induction in the dentate gyrus of freely moving rats. Surprisingly, we found significant changes in HDAC1 and HDAC2 activity in both the stimulated as well as the unstimulated hemispheres, with the largest increase in activity occurring bilaterally, 20 min after LTP stimulation. During this time point of heightened activity, chromatin immunoprecipitation assays showed that both HDAC1 and HDAC2 were enriched at distinct sets of genes within each hemispheres. Further, the HDAC inhibitor Trichostatin A enhanced an intermediate phase of LTP lasting days, which has not previously been associated with altered transcription. The inhibitor had no effect on the persistence of LTP lasting weeks. Together, these data suggest that HDAC activity early after the induction of LTP may negatively regulate plasticity‐related gene expression that is involved in the initial stabilization of LTP, but not its long‐term maintenance.